TOXIC IMPACT OF PHBNTHOATE ON SOME FUNCTIONAL ASPECTS OF NITROGEN METABOLISM IN TISSUES OF THE FISH CHANNA PUNCTATUS - Rao, K Sivaprasada; Rao, K R S Sambasiva; Babu, K Sreenivasa; Rao, K V Ramana (Indian Journal of Fisheries, 2011)
The tissue total proteins decreased with a raise in the free amino acid level in the fishes exposed to sublethal concentrations of phenthoate. However, ammonia and urea contents and the activity levels of glutamate dehydrogenase showed variable trend among the tissues during phenthoate intoxication. The results are discusssed in relation to the adaiptability of the fish by recycling the toxic ammonia to the less toxic urea and towards the synthetic processes under phenthoate toxic impact.